(untitled) (Advances in Knowledge Representation, 2023)
It is with great pleasure that I write this Editorial, after all it is a new issue of the thematic series “Knowledge Management (KM) – structures, models and tools”. This topic, extremely relevant to the area of GC, had many submissions, articles of excellent quality, which made it necessary to create a new selection of relevant articles, no less important than those already published in the previous issue.